Fluvial morphology and sediment dynamics: analysis of the downstream effects of the Madeira River hydroelectric complex - Santos, Mariano Vieira dos; Duarte, Miqueias Lima [UNESP]; Silva, Tatiana Acacio da [UNESP]; Costa, Heron Salazar; Braz Vaz, Marcos Andre (Revues Org, 2020)
Brazil has a rich density of superficial water bodies in its territory, this is associated with one of the largest potentials for hydroelectric power generation in the world. This potential has gradually been explored with the installation of hydroelectric projects over the years. In 2016, two hydroelectric plants were put into operation in the course of the Madeira River (Jirau and Santo Antonio hydroelectric). This study evaluated the fluvial morphology and the depositional dynamics of sediment downstream of these ventures, using data on the concentration of suspended sediments (CSS), and data from the orbital sensor Landsat 5 and 8 processed using the QGIS software. The results showed that there were physical alterations in the fluvial canal along the evaluated stretch, highlighting the erosion in the margins and the emergence of fluvial sand bank. Although the spatial analysis indicates an increase in river sand banks along the study area, the statistical analysis did not indicate significant differences between the CSS concentrations after the installation of hydroelectric enterprises.
Keywords: Fluvial geomorphology; River sediments; hydroelectric plants; Porto Velho